Art dealers and the great masters of painting - Ponzio de León, Carlos Alejandro (Estudios Económicos de El Colegio de México, 2015)
This paper presents a model on the relationship born during the Renaissance, between artists and dealers. It establishes the conditions that made possible such an arrangement. The model explains why this contract functioned properly among minor painters, and why the Great Masters did not got involved on it. Finally, the model studies the relationship between the number of artists signed under one single dealer and the marketing and promotional cost of the works of art.